Points of View in the Short story "The Lady with the Dog" by Anton Pavlovich Chekov (Slavic Studies, 2024)
The study is an attempt to re-examine the way in which in a short story from the period of realism under the title “The Lady with the Puppy” by A.P. Chekhov actualizes the ambiguous and subjective representations of reality. The analysis of points of view based on a structuralist, but also a philosophical perspective explains the dependence between the subject and the representation of objects and events in the world.